Unlocking the mysteries of cataloging : - Haynes, Elizabeth (Libraries Unlimited, 2005)
Supplementing existing textbooks with exercises that allow practice in description, classification, subject analysis, and MARC 21, this workbook pinpoints problem areas that arise in the cataloging of a wide variety of materials in public, school, special, and academic library settings. Real title pages and other necessary materials are used throughout. AACR2 rule numbers are included, as well as questions for consideration. MARC records are provided for some 50 of 150 exercises. The book companion Web site (http://www.lu.com/workbook) has a section for students and a password protected section for instructors who adopt the book for courses. The instructor's Web site includes MARC records for all exercises. This book will appeal to cataloging students as necessary practice for sharpening their skills, as well as to beginning catalogers in the large library environment. It will be a valuable addition as individual study material and for in-house training of catalogers.